A giant neobladder stone with insignificant symptoms: A case report and literature review - Gu, Jun; He, Zexi; Li, Haihao; Liu, Yijie; Wang, Haifeng; Huang, Yinglong; Ding, Mingxia (Frontiers in Surgery, 2023)
Background: Giant neobladder lithiasis after orthotopic bladder replacement is an infrequent but important long-term complication, which should be diagnosed and treated early. If left untreated, it may eventually lead to irreversible acute kidney injury and seriously affect the patients' quality of life. We hereby present a rare case of a massive neobladder stone after radical cystectomy with orthotopic neobladders construction, with a challenging stone extraction process. Case presentation: A 70-year-old female patient presented with a massive neobladder stone 14 years after radical cystectomy with orthotopic neobladders construction. Computed tomography scan showed a large elliptic stone. The patient underwent suprapubic cystolithotomy surgery, which resolved her giant stone in neobladder. The giant bladder stone removed was 13*11.5*9cm, with a total weight of 903 g. To date, the follow-up time is 4 months, and no pain, urinary tract infections, or other abnormalities suggestive of fistula were found. Conclusions: Imaging examination is useful for detecting neobladder lithiasis occurring after orthotopic neobladders construction. Our experience demonstrates that open cystolithotomy is an appropriate therapeutic method for the late complication of giant neobladder stone.